Intensitas Serangan Hama Daun, Pertumbuhan Dan Hasil Tanaman Sawi (Brassica juncea L.) Yang Diaplikasi Dengan Beberapa Konsentrasi Dan Frekuensi Larutan Daun Galam (Melaleuca cajuputi) - Zahrawati Zahrawati; Samharinto Soedijo; Hilda Susanti (EnviroScienteae, 2021)
Research on the intensity of leaf destroying pests, growth and yield of mustard (Brassica juncea L.) which was applied with several concentrations and frequency of galam (Melaleuca cajuputi) leaf solution has been carried out. The research was carried out at the Banjarbaru State Vocational School in March - June 2020 using a factorial completely randomized trial design. The first factor is the concentration of galam leaf solution application (20, 40, 60 and 80 ml/l) and the second factor is the frequency of application of galam leaf solution (1, 2 and 3 times a week). The control used in this study was without treatment which was placed separately outside the experimental design. The results showed that the interaction between the concentration level and the frequency of galam leaf solution had no effect on the intensity of leaf destroying pests and mustard plant yields, except for crude protein. The combination interaction between the concentration of 80 ml of galam leaf solution/l and the application frequency of 3 times gave the highest amount of crude protein. When compared with the control, the mustard plants that received the application of galam leaf solution showed a lower intensity of pest attack at 2 WAP with an attack intensity of 16.15%, as well as better growth and yields for plant height (3 and 4 WAP). leaves, total wet weight, crown weight, crude fiber and crude protein.